أحكام نشوز الزوجة في ضوء الفقه الإسلامي والقانون الأفغاني وتطبيقاتها المعاصرة في أفغانستان: The Ruling on Wife’s Rebellion in Light of Jurisprudence and Afghan Law and Its Contemporary Applications in Afghanistan - Naeem Hakimi, Mohammad; R.M. Elshobake, Mohammad; Bin Jaapar, Ghazali (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث يتناول البحث أحكام نشوز الزوجة في الفقه الإسلامي والقانون الأفغاني وتطبيقاته المعاصرة، حيث يكمن مشكلة البحث في التباين بين الأحكام الشرعية والتطبيقات القانونية والعرفية. يهدف البحث إلى توضيح مفهوم النشوز، وبيان أحكامه، وتحليل موقف القانون الأفغاني منه، واستعراض تطبيقاته المعاصرة. يعتمد على المنهج الاستقرائي والتحليلي والمقارن لاستقراء النصوص الشرعية وتحليها قانونيًا. وخلص البحث إلى أن الفقه الإسلامي وضع مراحل لعلاج النشوز، بينما يتأثر القانون الأفغاني بالفقه الحنفي والعرف القبلي، ويوصي بمراجعة الأحكام الشرعية وقوانين الأفغانية، ونشر الوعي الأسري. ABSTRACT The study examines the rulings on a wife’s rebellion(nushuz) in Islamic jurisprudence and Afghan law, as well as its contemporary application. The research problem lies in the discrepancy between Islamic rulings, legal applications, and customary practices. The study aims to clarify the concept of nushuz, outline its rulings, analyze Afghan law’s stance on the matter, and review its modern applications. It employs the inductive, analytical, and comparative methodologies to examine Islamic texts and analyze them legally. The study concludes that Islamic jurisprudence has established gradual steps to address nushuz, while Afghan law is influenced by the Hanafi School and tribal customs. It recommends reviewing relevant laws, strengthening the role of Sharia courts, and promoting family awareness.